An Overview Of Routing Protocols For Mobile Ad-Hoc Network - Bano, A; Yadav, R.K; Namdeo, V (International Journal of Computer Sciences and Engineering, 2025)
In case of ad hoc network, there is no provision for centralized control over network resources and the routing operations. Each node manages the communication links itself, updates the routing information to adopt the variations in topology. Ad hoc networks uses the shared channel and any node can transmit the data at any time over the network using shared channel but during the data transmission, any other node can also try for the data transmission which can lead to the congestion and contention over the shared channel and finally results in collision. For the better channel utilization, there are many solutions has been developed that can control the shared channel utilization in order to reduce collision and to enhance network performance. This survey paper contains a study of various kind of routing protocols used in communication systems whether it may be wired communication or may be wireless or sensor network system but still main focus is towards those routing protocols which are mostly suitable to Mobile Ad-hoc Networks